Mindfulness for adaptation to analog and new technologies emergence for long-term space missions - Le Roy, Barbara; Martin-Krumm, Charles; Trousselard, Marion (Frontiers in Space Technologies, 2023)
Long-term space missions require a good understanding of human adaptation to hostile environments in space. Some professional environments have space constraints that are isolating, confined, extreme, or unusual constraints. They can serve as space analogs for studying challenge adaptation as their environmental constraints disrupt the balance between the demands of the environment and the resources mobilized by individuals. This disruption in homeostasis leads to increased stress, decreased performance, and poor overall health for these professionals. Nevertheless, as analogs, these professional environments can also offer information for better identifying the individual psychological and cognitive resources that are effective in adapting to the constraints caused by these exceptional environments. Studies suggest that mindfulness (i.e., awareness that emerges by paying attention purposefully, in the present moment, without judgment to the experience that is unfolding moment by moment) may be a relevant candidate for dealing with these issues. Thus, we address mindfulness as a relevant psychological resource to face the constraints of space missions based on experiences in analog environments and military contexts. We propose to open discussions on new countermeasures focused on developing mindfulness, especially through the use of new technologies (e.g., “immersive reality” and others), to increase adaptation to the space environment and offer programs tailored to the needs of astronauts for long space journeys.